(untitled) (Journal of Education, Humanities, and Social Research, 2025)
This study investigates the impact of teacher feedback on students’ learning motivation, self-efficacy, and engagement in online learning environments. Grounded in Self-Determination Theory (SDT), the research explores how different types of feedback — cognitive, affective, and metacognitive — satisfy students’ psychological needs for autonomy, competence, and relatedness. A mixed-methods approach was employed, combining quantitative experimental data with qualitative interview insights. The findings reveal that affective feedback significantly enhances emotional engagement and self-efficacy, while metacognitive feedback promotes self-regulated learning and long-term retention. Cognitive feedback, though effective in improving task performance, has a limited impact on motivation unless paired with emotional or metacognitive elements. The study also highlights the importance of timely, personalized, and multimodal feedback in online education. These results provide practical implications for educators and online learning platforms, suggesting that optimizing feedback strategies can significantly improve student outcomes. The study contributes to the literature by integrating SDT with empirical research on feedback in online education, offering a framework for designing feedback practices that address students’ psychological needs.